Penerapan X Means Clustering Pada UMKM Kab Banyumas Yang Mendukung Mega Shifting Consumer Behavior Akibat Covid-19 - Rifki Adhitama; Auliya Burhanuddin; Atik Febriani (Journal of INISTA, 2022)
The Covid-19 has become a epidemic that is troubling the public because of the extent and speed of the virus spreading. The Covid-19 has resulted in people being unable to move outside their homes freely so that household consumption has decreased. This condition is similar to the crisis in 1997-1998, where MSMEs and small traders could survive. In Banyumas district, the percentage of MSMEs are in the large, medium, and small groups that can support the habit of Mega Shifting, or businesses that can be done at home so that they can be an economic savior in the covid-19. Clustering is a method of grouping similar objects which are taken from several criteria. X-Means is a grouping method that can be used to effectively calculate the value of K. As for testing the quality of a cluster using the Purity test method, it is said to be "Good" if the results of this Purity are close to 1. The total of MSMEs in the Banyumas district which be grouped is 27,574 MSMEs. The purity based on the results of the cluster is 0.9892 (3 groups), 0.9894 (4 groups), 0.9928 (5 groups), and 0.9677 (6 groups). In 3 groups, the results of grouping are 58 MSMEs belong to large groups, 381 MSMEs belong to medium groups, and 26,602 MSMEs belong to small groups. The recommended MSMEs sectors to face mega shifting are food stalls, culinary, agriculture, snacks, traders, craftsmen, workshops, furniture, constructions, and grocery stores.